The Effect of Mandala Coloring on Reducing Anxiety in Students of the Faculty of Psychology UIN Raden Fatah Palembang - Mulyati; Atin Hafizatul Aini; Iffah Tsabita Ikhsani; Nadia Dwi Cahyani; Septia Anggraini; Sayid Mubarak; Annisatul Muffidah; Dian Kurniati; Indah Nabilla Nur Lutfiyyah Zariyatan; Cindy Adelia (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
Anxiety is a psychological phenomenon that is commonly felt by everyone, especially people who frequently interact with crowds. Anxiety can happen to anyone, including students. students who are indicated to experience anxiety do not have a clear picture of their future. Coloring can be used as an alternative as an effort to reduce anxiety. Doing coloring for a long time tends to increase anxiety for related individuals. The main objective to be investigated in this study is whether the presence of mandala coloring treatment can affect the student's anxiety level. This study uses a quantitative experimental research approach. The experimental design used was a quasi-experimental design with a pre-test and post-test control group without any randomization process. This study used 32 university students as respondents who were experiencing mild to severe anxiety aged around 19-22 years. The results of the research analysis using the Paired Sample t-Test analysis , from the analysis results obtained the value of t = 2.445 with a sig (2-tailed) of 0.020 < 0.0 5 . It can be concluded that there is an effect of coloring mandalas on reducing anxiety in students of the Faculty of Psychology Uin Raden Fatah. Meanwhile, in the analysis between the control group and the experimental group using the Independent Sample t-Test, the output obtained a sig (2-tailed) value of 0.103 > 0.05, it can be concluded that there is no difference in the average results of anxiety levels in the experimental group and control group.